Morphometric study of jugular foramen in Tamil Nadu region - P Vijisha; Arun Kumar Bilodi; Lokeshmaran (Wolters Kluwer Medknow Publications, 2013)
Background and aims: Jugular foramen is an important foramen transmiting a number of structures at the base of the skull. Various tumours and infiltrating inflammatory processes are associated with this foramen. Hence, present study was taken up to study morphometry of the jugular foramen in human skulls in Tamil Nadu region. Material and methods: A total number of 60 jugular foramina were examined from 30 adult dry skulls of unknown age and sex. Measurements were taken using Vernier Calipers. Results were analysed statistically. Results: The length, width and area of jugular foramen of right side were compared with left side. Predominance of one of the two foramina was found in 86.6% (26): Predominance on right was 76.6% (23) and on left was 10% (3).The presence of partial septum was found around 73.3% on right side and 80% on left side respectively. Dome was present only 26.6% on right side and 3.33% on left side but in 70% of skulls it was present bilaterally. Conclusion: The morphometric variations in the skulls of Tamil Nadu region are probably ethnic and racial. The metric information is of use to the neurosurgeons dealing with the region.